2018
DOI: 10.31951/2658-3518-2018-a-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Modern changes in the ecosystem of Lake Onego with climate warming

Abstract: We have shown the changes in the ecosystem of Lake Onego 1 with climate warming over the past 30 years. Due to climate warming in winter, the river runoff increases, as well as the flow of allochtonic substances into the lake. With the increased runoff of the Shuya River, the main tributary of the Petrozavodskaya Guba (Bay), there is an additional influx of iron and phosphorus to the lake combined with the humus substances. Deep-water benthic communities in the lake become depressed. Therefore, in the past thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Due to high quantitative indicators and production rates, it is quickly included in the ecosystem processes of the transformation of matter and energy. The perch nutrition includes the new species and thereby becomes included in food chains [23]. The penetration of G. fasciatus into Lake Ladoga and Lake Onega led to an increase in the productivity of benthic communities and the more efficient utilization of energy entering the littoral area.…”
Section: Discussion: Is It Possible To Recover the Lakes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to high quantitative indicators and production rates, it is quickly included in the ecosystem processes of the transformation of matter and energy. The perch nutrition includes the new species and thereby becomes included in food chains [23]. The penetration of G. fasciatus into Lake Ladoga and Lake Onega led to an increase in the productivity of benthic communities and the more efficient utilization of energy entering the littoral area.…”
Section: Discussion: Is It Possible To Recover the Lakes?mentioning
confidence: 99%
“…This paper is based on an analytical review of published studies characterizing the natural state of the lakes before industrial activity [13][14][15][16][17][18]; changes in the main indicators of the polluted bays, which occurred in the mid 1960-1970s of the last century up to the 2000s [19][20][21]; and the state of the ecosystems in the same bays after stopping the pollution [22][23][24][25]. In this review, attention is focused on the main parameters of water chemistry and indicators of phytoplankton, zooplankton, benthos, and fish condition, which reflect ecosystem changes during different periods for Volkhov Bay of Lake Understanding the impact of anthropogenic contamination on aquatic ecosystems and their subsequent recovery as a result of decreasing anthropogenic stress is important for successful environmental management.…”
Section: Introductionmentioning
confidence: 99%
“…The Republic of Karelia (Northwest Russia) has a developed hydrographic network of more than 60 thousand lakes and 23 thousand rivers (Filatov, Kukharev, 2013). These freshwater ecosystems are most susceptible to the anthropogenic in uence in a changing environment (Filatov et al, 2018). Studying small urban lakes showed that they are subject to signi cant pollution from industry and transport .…”
Section: Introductionmentioning
confidence: 99%